Keabsahan Surat Keterangan Ahli Waris Yang Dibuat oleh Kepala Desa/Lurah dan Camat Untuk Warga Negara Indonesia Asli - Rohmatin, Siti; Widhiarto, Aran Eko; Sjafi'i, R. Imam Rahmat (Universitas Negeri Malang, 2022)
This study aimed to analyze the registration of land rights based on inheritance and the legality of the heir certificates made by the headman and district head. The type of research used in this study was normative juridical with a statutory and conceptual approach—sources of data obtained from primary, secondary and tertiary legal materials. The data analysis technique used a systematic method. The results showed that the registration of land rights due to inheritance required an heir letter. However, an heir certificate signed by the heirs and having the support of the headman and district head was not sufficient evidence but should obtain legality. Therefore, the making of heir certificates became overlapped between the heirs and village officials, especially regarding the legality of the cover letter.